Evaluation of Breast-Feeding Promotion Policy in Cipto Mangunkusumo Hospital Jakarta - Rulina Suradi; Dewi Anggraeni Wisnumurti (Paediatrica Indonesiana, 1995)
The purpose of this prospective cohort study was to evaluate the breastfeeding promotion program m Dr. C1pto Mangunkusumo general hospital which we started m 1991. The study was done from July 1992 until March 1993. During that time. We could follow 249 mother-infant pairs every month for 4 months. Results: 1. Babies who received only breast milk during hospital stay did not lose more weight if compared to babies who got some formula. 2. Not a single baby lost weight more ~10% during hospital stayÂ· Prelacteal feeding delayed the adequacy of breastmilk; 4. Though prelacteal feeding once or twice by spoon did not interfere with full breast feeding at the age of 4 months, yet mothers whose babies were given prelacteal feeding started to give supplementary food earlier; 5. Family income places a role in the decision to give early food supplement.